Comparative study of the legal terminology in bibliographic systems in the light of the code of civil procedure brazil - Fogaça, Maria Giovane (2021)
Vocabulary analyzes the specialized for knowledge representation within the legal department as query language, that in order to represent concepts through terms to obtain a consistent language and compatible demand in specialized areas. Focusing on the analysis of the terminology of legal systems presented in Decimal Universal Classification (UDC) and Decimal Classification of Law and / or Doris Classification (CDDir) according to the Civil Procedure Code. Regarding to methodology, it was characterized by a bibliographical and documental research, in scope of the work goals, it was characterized by a descriptive and exploratory research, with comparative procedure, and also qualitative approach. Thus, it was analyzed identified terms in the Civil Procedure Code, included in the Appeal Zone. According to the achieved results analized, it was possible to perceive some aspects, such as the systems temporality, training concept, the hierarchical relationship, the equivalence relation, etc.., and thus achieving the main purpose of this study. It concludes that the systems classification, UDC and CDDir, may be compatible with the Civil Procedure Code.